Influence Of The Teachers’ Teaching Styles On The Academic Achievement And Motivation Amongunderachiving’ Gifted Students In Saudiarabia - Mohammed Ali H, Alqarni (2020)
In the last decades, giftedness education in Saudi Arabia has attained a great attention from the governmental authorities. Several efforts were performed to provide gifted student with appropriate education that meets their abilities. However, recent researches had revealed the existence of the underachievement phenomena among gifted students in the country. What is more worrisome and perplexing or disappointing is the problem of underachievement among the gifted students. The present study intends to examine this problem of.the academic achievement and motivation of underachiving’ students and the influencing factors in the context of Saudi Arabia.